2008
DOI: 10.1007/s11302-008-9128-9
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Leydig cells express multiple P2X receptor subunits

Abstract: ATP acts on cellular membranes by interacting with P2X (ionotropic) and P2Y (metabotropic) receptors. Seven homomeric P2X receptors (P2X 1 -P2X 7 ) and seven heteromeric receptors (P2X 1/2 , P2X 1/4 , P2X 1/5 , P2X 2/3 , P2X 2/6 , P2X 4/6 , P2X 4/7 ) have been described. ATP treatment of Leydig cells leads to an increase in [Ca 2+ ] i and testosterone secretion, supporting the hypothesis that Ca 2+ signaling through purinergic receptors contributes to the process of testosterone secretion in these cells. Mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
(87 reference statements)
2
28
0
Order By: Relevance
“…The presence of ecto-5 0 -nucleotidase in interstitial cells was detected in both macrophages, which also express NTPDase1, and Leydig cells. Although the P2 receptor pattern in mouse Leydig cells (Antonio et al 2009;Glass et al 2001) and extracellular ATP stimulation of testosterone secretion (Foresta et al 1996) have been welldefined, adenosine receptors have not yet been identified at interstitial cells and would be an interesting issue to address.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ecto-5 0 -nucleotidase in interstitial cells was detected in both macrophages, which also express NTPDase1, and Leydig cells. Although the P2 receptor pattern in mouse Leydig cells (Antonio et al 2009;Glass et al 2001) and extracellular ATP stimulation of testosterone secretion (Foresta et al 1996) have been welldefined, adenosine receptors have not yet been identified at interstitial cells and would be an interesting issue to address.…”
Section: Discussionmentioning
confidence: 99%
“…IVM-sensitive currents were also detected in numerous mouse cell types, including macrophages (Sim et al, 2007), cortical neurons (Lalo et al, 2007), glial cells (Raouf et al, 2007), ventricular myocytes (Shen et al, 2006), submandibular gland ductal cells (Pochet et al, 2007), and Leydig cells (Antonio et al, 2009). IVM was also used to study the functional interactions of P2X4R with other members of this family of channels (Alqallaf et al, 2009;CasasPruneda et al, 2009).…”
Section: Ivermectin As the P2x4 Receptor-specific Modulatormentioning
confidence: 99%
“…Thus, activation of p38 MAPK may be a critical mechanistic step of convergence in the P2X7 and P2X4 receptor signaling pathways in neuropathic pain. P2X7 and P2X4 receptors also interact to form complexes with unique channel properties (Antonio et al, 2009;Boumechache et al, 2009;Casas-Pruneda et al, 2009;Guo et al, 2007;Nicke, 2008). This raises the interesting possibility that structural and functional interactions, as well as converging signaling pathways, might be critical cellular mechanisms that underlie involvement of microglial P2X7 and P2X4 receptors in neuropathic pain.…”
Section: Role Of Microglial P2x7 Receptors In Neuropathic Painmentioning
confidence: 99%